Progesterone Metabolites Inhibit the Human Ether‐a‐go‐go‐Related Gene and Predict QT Interval Length. (12th December 2019) - Shugg, Tyler; Egly, Christian; Stamatkin, Chris W.; Patil, Avinash S.; Tisdale, James E.; Overholser, Brian R.
Abstract: A decrease in the human ether‐a‐go‐go‐related gene ( hERG /KCNH2)‐related channel has been linked to intrauterine fetal death. The formation of cytochrome P450 (CYP) 3A‐mediated progesterone metabolites, 6‐beta‐hydroxy‐progesterone (6β‐OHP) and 16α‐hydroxy‐progesterone (16α‐OHP), is variable among adults and differs from fetal metabolism. The primary objective of this study was to assess the potential for progesterone metabolites to inhibit hERG ‐related current and predict QTc intervals. Whole‐cell voltage‐clamp electrophysiology was performed on human embryonic kidney 293 cells stably expressing hERG exposed to progesterone or metabolites. Both 6β‐OHP and 16α‐OHP positively shifted the voltage dependence of activation relative to vehicle from ‐4.0 ± 0.8 to ‐0.3 ± 0.8 mV, P < .01; and 1.0 ± 0.6 mV, P < .01, respectively. In addition, 6β‐OHP decreased maximal outward tail currents from 49.4 ± 4.9 to 32.5 ± 4.1 pA/pF, P < 0.01, and reduced the expression of fully glycosylated hERG by 42%. Healthy female subjects were administered progesterone 400 mg orally for 7 days, ibutilide 0.003 mg/kg was infused, and serial electrocardiograms and blood samples collected. Relationships between rate‐corrected QT intervals (QTcI) with circulating hormones and metabolites were assessed. The 6β‐OHP and 16α‐OHP metabolites were independent predictors of QTcI intervals prior to and following ibutilide administration. In conclusion, the progesterone metabolites formed via CYP3A cause inhibitory effects on hERG channels and predict QTcI intervals in healthy women pretreated with progesterone. Further study into maternal and fetal exposure to these metabolites and potential to prolong cardiac repolarization is warranted.